Going to church in medieval England - Orme, Nicholas (Yale University Press, 2021)
"An engaging, richly illustrated account of parish churches and churchgoers in England, from the Anglo-Saxons to the mid-sixteenth century. Parish churches were at the heart of English religious and social life in the Middle Ages and the sixteenth century. In this comprehensive study, Nicholas Orme shows how they came into existence, who staffed them, and how their buildings were used. He explains who went to church, who did not attend, how people behaved there, and how they--not merely the clergy--affected how worship was staged. The book provides an accessible account of what happened in the daily and weekly services, and how churches marked the seasons of Christmas, Lent, Easter, and summer. It describes how they celebrated the great events of life: birth, coming of age, and marriage, and gave comfort in sickness and death. A final chapter covers the English Reformation in the sixteenth century and shows how, alongside its changes, much that went on in parish churches remained as before."--